RESILIENSI TANTANGAN BENCANA BANJIR DI LAMPUNG : PERAN KEPADATAN DAN PENDIDIKAN - Mukaromah, Laila; Safitri, Gita; Listiana, Filza; Sari, Nur Permata; Sobita, Nindya Eka; Purwaningsih, Vitriyani Tri; Hudani, Muhammad Mufti (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Flood disasters pose a serious threat to communities worldwide, including in Lampung Province, Indonesia. Previous research has highlighted the roles of population density and education level in influencing community resilience to flood disasters. However, deeper investigations are needed to understand the dynamics of flood disaster management in Lampung. The aim of this study is to investigate how population density and education level affect flood disaster management in eight districts and cities in Lampung province between 2019 and 2023. Through this approach, it is expected to gain deeper insights into the factors affecting community resilience to flood disasters in Lampung. t is expected that the research's conclusions will serve as a foundation for future mitigation and adaptation plans that are more successful and will also greatly advance knowledge of the dynamics of flood disaster management in Lampung in both domestic and international contexts. Keywords : Flood disasters, Community resilience, Population density, Education level,